On terminology and topographic classification of the lingual lymph nodes - S. R. Gvetadze; E. A. Roshchina; A. M. Mudunov; A. I. Karseladze; J. Sun; M. Lv; X. Yang; N. N. Ayzikova; K. D. Ilkaev (Опухоли головы и шеи, 2022)
A review of accumulated international clinical experience and prognostic significance calculations of metastatic involvement of the lingual lymph nodes is given. Anatomical terminology of lingual lymph nodes and its contradictive aspects are discussed. It is shown that metastatic lesions of the lingual lymph nodes posses high prognostic value, therein a topographic anatomic classification of the lingual lymph nodes is needed to increase the efficiency of diagnosis and augmenting of the oncologic treatment results. This classification should be unified to avoid misunderstanding between researchers.